Evaluation of Free Online Machine Translations for Croatian-English and English-Croatian Language Pairs - Seljan, Sanja; Brkić, Marija; Kučiš, Vlasta (2012)
This paper presents a study on the evaluation of texts from four domains (city description, law, football, monitors) translated from Croatian into English by four free online translation services (google Translate, Stars 21, InterTran and Translation Guide) and texts translated from English into Croatian by Google Translate.
Projekt MZOS
ENG